Pengaruh kesadaran merek, kualitas yang dirasakan, dan sikap merek pada , niat beli biskuit oreo di Surabaya - Claudia Bimantari (Journal of Business & Banking, 2018)
This study aims to determine the effect of Brand Awareness, Perceived Quality, and Brand Attitude toward Purchase Intention of Biscuit Oreo in Surabaya. This research is a survey one with causal relationship constructs, so questionnaire is the main data source. Questionnaire measured with Likert scale and then data analysis done using structural equation model using Amos 22.0 program. The results showed that Brand Awareness significantly influence Perceived Quality because the standardized regression weight is 0.354 with value of C.R of 2.974 and p value of 0.003. Brand Awareness Significantly influence Purchase Intention because standardized regression weight is 0.486 with value of C.R of 3.756 and p value of 0.000. Perceived Quality significant influence Brand Attitude because standardized regression weight is 0.311 with value of C.R of 2.618 and p value of 0.009. Perceived Quality does not significantly influence Purchase Intention because standardized regression weight is 0.236 with value of C.R of 1.905 and p value of 0.057. Brand Attitude significantly influence Purchase Intention because standardized regression weight is 0.226 with a value of C.R of 2.015 and p value of 0.044